2014
DOI: 10.1155/2014/765832
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Oligomers for the Prevention and Treatment of Cancers

Abstract: Resveratrol (3,4′,5-trihydroxystilbene) is a naturally derived phytoalexin stilbene isolated from grapes and other plants, playing an important role in human health and is well known for its extensive bioactivities, such as antioxidation, anti-inflammatory, anticancer. In addition to resveratrol, scientists also pay attention to resveratrol oligomers, derivatives of resveratrol, which are characterized by the polymerization of two to eight, or even more resveratrol units, and are the largest group of oligomeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
75
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(77 citation statements)
references
References 72 publications
0
75
0
2
Order By: Relevance
“…One group of compounds that has shown promising and often higher potential anticancer activity than resveratrol itself are the so-called resveratrol oligomers, which are naturally occurring stilbenoids consisting of two to eight resveratrol subunits (Xue et al, 2014). For example, it has been reported that several resveratrol oligomers exert far higher cytotoxic effects on various tumor cell lines when compared with resveratrol (Ito et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…One group of compounds that has shown promising and often higher potential anticancer activity than resveratrol itself are the so-called resveratrol oligomers, which are naturally occurring stilbenoids consisting of two to eight resveratrol subunits (Xue et al, 2014). For example, it has been reported that several resveratrol oligomers exert far higher cytotoxic effects on various tumor cell lines when compared with resveratrol (Ito et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…eViniferin also shows the direct cytotoxicity (Xue et al 2014), anticancer, anti-inflammatory (Guschlbauer et al 2013), and neuroprotective (Nopo-Olazabal et al 2014) effects on various cancer cells. It was reported that e-viniferin could kill C6, Hep G2, HeLa, and MCF-7 cancer cell lines in a dose-dependent manner (Xue et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…eViniferin also shows the direct cytotoxicity (Xue et al 2014), anticancer, anti-inflammatory (Guschlbauer et al 2013), and neuroprotective (Nopo-Olazabal et al 2014) effects on various cancer cells. It was reported that e-viniferin could kill C6, Hep G2, HeLa, and MCF-7 cancer cell lines in a dose-dependent manner (Xue et al 2014). In addition, while e-viniferin has antitumoral effects on lymphocytes, myeloid cells, HL-60, HepG2 and human breast cancer cells as an antioxidant, it also prevents necrosis caused by reactive oxygen species (ROS) in normal rat fibroblast cells (Morales et al 2002;Piver et al 2003;Privat et al 2002;Zghonda et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of resveratrol include anti-oxidant and anti-aging properties, improvement of insulin sensitivity and reduction of cardiovascular disease risk (9-11). Previous studies have also indicated that resveratrol is able to function as a chemo preventive and chemotherapeutic agent in certain types of human carcinomas, including those of the colorectum, skin, liver, lung, pancreas, breast and prostate (8,(12)(13)(14). Previous studies suggesting that a dietary pattern rich in resveratrol may reduce the risk of ESCC (15).…”
mentioning
confidence: 99%